Developing English Instructional Materials by Combining YouTube and ABA (American and British Academy) Application - Syaripuddin, Rahmatullah (CV. Rayyan Dwi Bharata, 2023)
This research was based on the students’ problem regarding the English teaching, especially English materials where they have poor English skills because the lecturer did not have instructional materials related to their department, the media and method did not interesting, and instructional facilities did not enough to cover the learning process. The objective of this research was to develop English speaking materials based on modified ADDIE approach (Analyze, Design, Development, Implementation, and Evaluation). This research was conducted at the Biological students of Muhammadiyah University of Parepare, Indonesia. The method used in this research was developmental research which attempts to develop English learning material for English skills based on the modified ADDIE approach (Analyze, Design, and Development). The researcher applied design instructional as the research design. The researcher implemented some steps in developing English speaking materials; Need Analysis, Design, Development, Expert Validation, Revision, Try Out, and Final Product. The result of the research was The suitable materials for Biological students of Muhammadiyah University of Parepare were authentic materials. The development was coursebook which was designed to possibly for the students working on it. The materials were adopted from YouTube and ABA English. The instructional materials focused on input, process, and output. The students’ positive perception toward the instructional materials was in a very good value and the lecturer’s positive perception was also in very good value. It means that English for Biology instruction has a good quality in the form of the course map, lesson plan, lecturer’s manual, topic, video clips, materials, students’ worksheet, learning activities, and assessment